2001
DOI: 10.1183/09031936.01.00089401
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exposure to sulphuric acid on the early asthmatic response to inhaled grass pollen allergen

Abstract: Particulate sulphates, including sulphuric acid (H 2 SO 4 ), are important components of the ambient aerosol in some areas and are regarded as air pollutants with potentially important human health effects. Challenge studies suggest little or no effect of H 2 SO 4 exposure on lung function in asthmatic adults, although some epidemiological studies demonstrate an effect of acid species on symptoms in subjects with asthma. To date, the effect of H 2 SO 4 on allergen responsiveness has not been studied.The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Of the seven studies that evaluated participants with asthma, only Bylin et al (1988) did not provide information regarding medication status. Of the six studies with information regarding medication status, only the two studies by Tunnicliffe et al (1994Tunnicliffe et al ( , 2001 included participants who required regular use of inhaled corticosteroids. All of the studies that evaluated SO 2 indicated that study participants refrained from using medication for at least 12 h prior to exposure; the other studies that evaluated individuals with asthma did not provide information regarding withholding medication.…”
Section: Study Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the seven studies that evaluated participants with asthma, only Bylin et al (1988) did not provide information regarding medication status. Of the six studies with information regarding medication status, only the two studies by Tunnicliffe et al (1994Tunnicliffe et al ( , 2001 included participants who required regular use of inhaled corticosteroids. All of the studies that evaluated SO 2 indicated that study participants refrained from using medication for at least 12 h prior to exposure; the other studies that evaluated individuals with asthma did not provide information regarding withholding medication.…”
Section: Study Overviewmentioning
confidence: 99%
“…In the study by Tunnicliffe et al (2001), we identified one study participant as potentially sensitive to H 2 SO 4 , based on the magnitude of their response at both 100 and 1000 lg/m 3 H 2 SO 4 (Fig. 4).…”
Section: #*mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these studies have found an enhanced allergic response of asthmatics to allergen after exposure to ozone, nitrogen dioxide, and a combination of nitrogen dioxide and sulfur dioxide (Jorres et al 1996;Rusznak et al 1996;Strand et al 1998;Tunnicliffe et al 2001). Tunnicliffe and colleagues (2001) studied the effect of a 1-hr exposure to nitrogen dioxide (100 or 400 ppb) on airway responses to inhaled allergen in eight asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on 10 atopic asthmatic adults, particulate sulfuric acid exposure potentiated early asthmatic response to grass pollen allergen (Tunnicliffe et al 2001). Subjects were exposed to sulfuric acid particulates at concentrations of 0.1 and 1.0 mg/m 3 for 1 hr.…”
Section: Discussionmentioning
confidence: 99%